The International Criminal Court and the End of Impunity in Kenya - Nichols, Lionel. author. aut Link
XV, 267 p. 6 illus. in color.
Keywords: The period immediately following Kenya's 2007 presidential election left a shocking trail of atrocities, with over 1,000 people dead and countless thousands left victimised and displaced. In response, the International Criminal Court began a series of investigations and trials, promising no impunity for even the highest ranking perpetrators. When the country's president and vice-president were implicated in the crimes, the case took on worldwide significance. The International Criminal Court and the End of Impunity in Kenya is a five-year study addressing critical human rights issues with a global reach and is the first detailed account of the ICC's intervention in Kenya. It probes the relationship between the ICC and state institutions, known as positive complementarity, and asks whether the ICC's intervention led to an end to impunity. The author provides comprehensive analysis of the Waki Commission's sealed envelope, the government's attempts to establish a special tribunal and the trials in The Hague. He also provides in depth consideration of any influence the ICC's intervention may have had on the passing of a new constitution, the establishment of a truth commission and important reforms to the judiciary, police and witness protection programme. Documenting the effects of these interventions on the Kenyan people, and on the country's legal and judicial systems, the book provides vital lessons in global justice as it: •Details the ICC's involvement in Kenya in the aftermath of extreme violence and instability •Evaluates the ICC prosecutor's strategy of positive complementarity •Identifies optimal conditions for positive complementarity to be effective •Links cultures of impunity to state-sponsored corruption •Explores the possible impact of the ICC on national and global policy •Discusses implications in responding to future crimes against humanity Replete with official government sources, The International Criminal Court and the End of Impunity in Kenya is necessary reading for researchers and practitioners working in public international law, particularly those specialising in conflict and post-conflict states.